Comparing adsorption activity of raw Sepiolite and CTAB modified Sepiolite: kinetic and adsorption study for removal of Hg+ - Vaġzoğullar, Ali Ġmran; Uğurlu, Mehmet; Kula, Ġbrahim (International Journal of Environment, 2015)
In our study adsorption of Hg+2 ions from water solutions on Sepiolite (Sep) and Modified Sepiolite (MSep) with cationic surfactants namely cetyl trimethyl ammonium bromide CTAB was investigated. Different parameters were used to investigate such as contact time, pH and adsorbent dosage. The adsorption capacity of MSep and Sep was examined. Both particles were characterized with FTIR spectrum. According to the our results the equilibrium adsorption data corresponded to the Langmuir isotherm and qmax was 54,7 mg/g and 104,1 mg/g for Sep and MSep respectively. Kinetic parameters showed that pseudo-second-order adsorption kinetic model was the best model than the pseudo-first-order. MSep is more active adsorbent than Sep and it can be the best alternative adsorbent for removing of heavy metal from industrial waste water. In addition MSep can be used as adsorbent for removal of nonpolar toxic organic molecules, because sepiolite surface can be converted from hydrophilic form to hydrophobic form by CTAB resulting in increased the adsorption capacity. International Journal of Environment Vol.4(4) 2015: 19-31